Improving the Hardness of 3D Printable ABS Filament Through Thermal and Cooling Process Control - Nurlia Pramita Sari; Akhmad Faizin; Bayu Pranoto; Mochamad Muzaki; Firza Nurdin Maulana (Universitas Islam Raden Rahmat, Malang, 2025)
The properties of filament are widely recognized as critical factors influencing the performance of fused filament fabrication (FFF) in 3D printing. Acrylonitrile Butadiene Styrene (ABS) is frequently utilized in this process due to its high strength, durability, and availability. Nevertheless, the characteristics of the filament are highly dependent on processing parameters, particularly extrusion temperature and cooling method, which directly affect its mechanical behavior and dimensional stability. The objective of this study was to evaluate the effect of extrusion temperature and cooling medium on the hardness of ABS filaments produced using a single-screw plastic extruder. Experimental procedures were performed at three extrusion temperatures, namely 180 °C, 200 °C, and 220 °C, with cooling applied by water immersion and by air using a blower. The results demonstrated that air cooling produced superior hardness values and more consistent dimensional stability compared to water cooling. The optimum condition was observed at an extrusion temperature of 180 °C under air cooling, which resulted in the highest hardness values along the filament length (95.63HA average). These findings suggest that careful optimization of extrusion parameters, particularly the selection of an appropriate cooling method, is essential to improve filament quality for additive manufacturing applications.